Impact of Washing Chemistry Factors on Wool Fibre Shrinkage - Azeez Mutiu O (Chemistry and Biochemistry: Research Progress Vol. 6, 2025)
The washing chemistry variables, such as water, mechanical agitation, temperature, and spinning, are responsible for the efficient washing of fabrics. However, these factors can also contribute to fabric shrinkage. Fabric shrinkage during usage and processing is a challenge in the laundry and dry-cleaning industry. The fabric shrinkage might be a form of a decrease in the fabric’s dimensions when in use. This study intends to investigate the washing variables above and washing programs designed by the manufacturer so that the textile care service providers may have in-depth knowledge of their roles in maintaining delicate fabrics such as wool and preventive measures. This is an experimental study in which six fabric pieces were included. The variables under investigation were subjected to real-life washing operations in a washer extractor under varying conditions at a constant load for gravitation effects. The area shrinkage was calculated for each variable. The results showed that the machine manufacturer’s program for wool does not prevent wool shrinkage. The program Quick 30 shows a more aggressive effect and mechanical action on wool shrinkage. The findings also indicated that percentage area shrinkage increases as the temperature rises from 30°C to 40°C, and area shrinkage steadily approaches equilibrium at 60°C. Furthermore, findings suggested that percentage area shrinkage was not directly proportional to an increase in spinning speed. Machine default programs, variables manipulation indicated a significant reduction in fabric shrinkage, provided other variables remained fixed. Future researches need to be conducted on the different brands of washing machines available in the markets, as well as different configurations of washing wheel to verify manufacturers’ claims.